Physicians' cognitive approach to prognostication after cardiac arrest. (April 2022) - Steinberg, Alexis; Grayek, Emily; Arnold, Robert M.; Callaway, Clifton; Fischhoff, Baruch; Krishnamurti, Tamar; Mohan, Deepika; White, Douglas B.; Elmer, Jonathan
Abstract: Objective: Elucidate how physicians formulate a neurological prognosis after cardiac arrest and compare differences between experts and general providers. Methods: We performed semi-structured interviews with experts in post-arrest care and general physicians. We created an initial model and interview guide based on professional society guidelines. Two authors independently coded interviews based on this initial model, then identified new topics not included in it. To describe individual physicians' cognitive approach to prognostication, we created a graphical representation. We summarized these individual "mental models" into a single overall model, as well as two models stratified by expertise. Results: We performed 36 interviews (17 experts and 19 generalists), most of whom practice in Europe (23) or North America (12). Participants described their approach to prognosis formulation as complex and iterative, with sequential and repeated data acquisition, interpretation, and prognosis formulation. Eventually, this cycle results in a final prognosis and treatment recommendation. Commonly mentioned factors were diagnostic test performance, time from arrest, patient characteristics. Participants also discussed factors rarely discussed in prognostication research including physician and hospital characteristics. We found no substantial differences between experts and general physicians. Conclusion: Physicians' cognitive approach to neurologic prognostication is complex and influenced by many factors, including some rarely considered in current research. Understanding these processes better could inform interventions designed to aid physicians in prognostication.